Pengaruh Arus Modal Masuk (Capital Inflow) Terhadap Perekonomian di Indonesia - Ulfa Wahyuni; Dewi Zaini Putri (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This study aims to determine and analyze the influence of (1) foreign direct investment, (2) portfolio investment, and (3) foreign debt to the economy in Indonesia. The analysis used Ordinary Least Square (OLS) with multiple linear regression tests using time series data from 1986 to 2016. Data sources from the Central Statistics Agency, SEKI Bank Indonesia, World Bank. The results of this study are foreign direct investment, portfolio investment and foreign debt have a positive and significant impact on the economy in Indonesia. From the results of the study, the Indonesian government is expected to improve policies in the investment climate in Indonesia, including security, licensing and facilities and infrastructure, where the improvement of the investment climate will open employment opportunities and will improve the welfare of the community and make efforts to properly manage foreign debt provide benefits to improve the Indonesian economy